Pengaruh ukuran perusahaan, financial leverage, dividen payout ratio dan net profit margin terhadap tindakan perataan laba yang dilakukan oleh perusahaan automotive and allied product yang listing di BEI - Dina Hastria; Muhammad Rasuli; Nurazlina ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimes are to examine the impact of firm size, financial leverage, dividend payout ratio and net profit margin toward income smoothing in automotive and allied product company that listed on the Indonesia Stock Exchange.The population was automotive and allied products company which have a very tight competition, it can be seen from the model and system works which often change with new innovations so researchers interested to study at this company. The sample were selected by purposive random sampling method.The results of this study declare that the firm size has a significant impact on the income smoothing. While financial leverage, dividend payout ratio and net profit margin has no significant effect on the income smoothing. Adjusted R Square shows the value of 0.109. It means that 10.9% change in the income smoothing is affected by the determinant variables in the model while the rest (89.1%) is explained by other variables not included in the model. The small coefficient of determination in this study is caused by the independent variables tested that have a little relationship to the dependent variable.Keywords: Company Size, Financial Leverage, Dividend Payout Ratio and Net Profit Margin, Income Smoothing